The Effect of Competence, Workload, and Work Environment on Employee Performance with Work Motivation as an Intervening Variable (Case Study at Puskesmas Guntur II Demak) - Prabowo, Nunki Adhi; Rusdianti, Endang; Wardoyo, Paulus (Universitas Syiah Kuala, 2023)
This study aims to analyze the effect of competence, workload, and work environment on employee performance which is mediated by work motivation at the Guntur II Health Center in Demak. Health is an investment in human resource development. Therefore, employee performance is important for the Guntur II Demak Health Center because it cannot be separated from the results that play a role in consumer satisfaction. However, the performance of the puskesmas is still not optimal, which is caused by the target not being achieved as set. This study uses quantitative methods with census techniques. Data collection was carried out using a questionnaire technique with a population of 60 people as respondents, data analysis techniques using structural equation modeling, namely Partial Least Square (PLS) based on a Likert scale with a range of 10 (scale 1 to 10). Based on the results of the analysis using Smart PLS, the study found that workload and work environment had no effect on work motivation and employee performance, besides work motivation could not mediate workload and work environment. Work motivation has an impact on employee competence and performance. This also affects employee performance positively and significantly. Thus, work motivation can directly or indirectly mediate the relationship between competence and employee performance. Guntur Demak Health Center should pay more attention to increasing employee competence so that their work motivation increases.